The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1542/peds.2009-1678
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Practices of Cardiologists and Surgeons Who Manage HLHS

Abstract: Virtually all North American pediatric cardiologists and cardiac surgeons surveyed discuss a surgical intervention when counseling parents about the care of their child or fetus with HLHS. However, only a minority discuss all options. Most physicians recommend staged palliative surgery for management of HLHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Variation in patient cohorts, variable length of patient-clinician relationships, and a breakdown in interdisciplinary communication may all contribute to discordance among clinicians of different specialties. [35][36][37] Less than one-third of clinicians believed that ACD typically happen at the right time in the course of illness. More than 90% responded that discussions of overall goals of care should happen either during diagnosis or during a time of stability.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in patient cohorts, variable length of patient-clinician relationships, and a breakdown in interdisciplinary communication may all contribute to discordance among clinicians of different specialties. [35][36][37] Less than one-third of clinicians believed that ACD typically happen at the right time in the course of illness. More than 90% responded that discussions of overall goals of care should happen either during diagnosis or during a time of stability.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the critically important HLHS has been particularly successful, allowing extensive counseling of families, planning of surgeries and even in rare cases fetal interventions. According to a study by Prsa et al [14] in the case of antenatal diagnosis of HLHS allowing for prenatal counseling by cardiologist and cardiothoracic surgeons, 98.8% discussed continuation of pregnancy with staged palliative surgery after birth, 56.9% discussed continuation of pregnancy with compassionate care after birth, and 74.3% discussed termination of pregnancy. Due to the poor prognosis of this lesion and the variety of approaches, being able to counsel families prenatally becomes particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As the outcomes of the staged procedures improve, an increasing number of children with complex heart conditions have survived into adulthood. [2][3][4][5] More patients are now undergoing staged procedures [6][7][8] but the trend in long-term inpatient cost and care needs for this population are unclear. Using hospital billing data associated with encounters, Keren et al (2012) have shown that the cumulative costs of the 10 most expensive pediatric conditions in the US accounted for approximately one third of the standardized costs for all pediatric visits to hospital, and single-ventricle congenital heart defects such as hypoplastic left heart syndrome (HLHS) ranked 7 th on the list.…”
Section: Accepted Manuscriptmentioning
confidence: 99%